Digestibility of Acacia macracantha attenuated in secondary compounds and Acacia polyphylla in rabbit diets - Carrero-Prato, Eloillin (2025)
This study, conducted in Lara State, Venezuela, aimed to evaluate the effects of dolomitic lime treatment on Úveda pods to reduce secondary compounds (CSAs) and its impact on nutrient intake and digestibility in rabbit diets. The trial utilized iso-protein diets with varying inclusion levels of Acacia macracantha pods (Pam) and Acacia polyphylla foliage (Fap), alongside different levels of lime treatment (0.5% and 1.0%) on Pam. The experimental design was completely randomized with 5 treatments: T0 (commercial balanced feed); T1 (30.0% Cf, 2.0% vitamins and minerals (vit), 7.5% M, 45.0% Fap, and 15.5% Pam); T2 (30.0% Cf, 2.0% vit, 7.0% M, 45.0% Fap, and 16.0% Pam); T3 (30.0% Cf, 2.0% vit, 7.5% M, 30.0% Fap, and 30.5% Pam) and T4 (30.0% Cf, 2.0% vit, 7.0% M, 30.0% Fap, and 31.0% Pam). In this way, 5 repetitions per treatment: one rabbit/cage/experimental unit (Californian rabbit, 1.286 ± 0.045 kg of initial live weight). The trial lasted 12 days: 7 of habituation and 5 of collection. The study focused on evaluating the intake and digestibility of several nutrients: dry matter (DM), organic matter (OM), cell wall content (neutral detergent insoluble fiber, NDF), and crude protein (CP). These variables were examined to assess the effectiveness of different dietary treatments in rabbits. Significant differences were found regarding DM intake. The highest was for T0 (141.0 g/animal/d), followed by T3 and T4, with 84.8 g/animal/d and 85.5 g/animal/d, respectively. The digestibility of DM and NDF had the highest values in T0 (69.3% and 51.8% in that order), followed by T3 (52.0% and 39.7%). Regarding CP, the highest digestibility was for T0 (81.8%), secondly by T3 (41.3%). This allows to conclude that lime treatment did not completely neutralize the enzymatic inhibitor of protein digestibility present in Pam, being the best treatment T0, and then processed food T3 and T4. Further studies are recommended to assess long-term impacts on growth and nutrient utilization.